2018
DOI: 10.1021/acs.cgd.8b00990
|View full text |Cite
|
Sign up to set email alerts
|

Diastereomeric Salt Formation by the γ-Amino Acid RS-Baclofen and L-Malic Acid: Stabilization by Strong Heterosynthons Based on Hydrogen Bonds between RNH3+ and COOH/COO Groups

Abstract: Baclofen (BAC) is an important chiral active pharmaceutical ingredient for the treatment of specific neurological disorders that is commercially available only as RS-BAC (racemate). Using the liquid-assisted grinding technique, combination of RS-BAC with DL-MA in 1:1 stoichiometric ratio yielded a crystalline solid phase mixture of the enantiomeric salts R-BAC:L-MA and S-BAC:D-MA. Single-crystals suitable for SCXRD analysis of R-BAC:L-MA were obtained by fractional crystallization from a solution of RS-BAC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 81 publications
(163 reference statements)
0
12
0
1
Order By: Relevance
“…Baclofen, a drug used to treat muscle spasticity, for instance from spinal cord injuries, is one of the chiral drugs still sold in a racemic form. Previous research has shown that the two baclofen enantiomers have different bioactivities. , Accordingly, many processes have been developed to produce enantiopure baclofen or to separate the enantiomers of baclofen: asymmetric synthesis, chiral chromatography, , preferential crystallization, and resolution by diastereomeric salt formation. , The latter method is widely applied in industry since it is easy to scale up economically. The resolution occurs by forming diastereomeric salts from the racemate and a chiral resolving agent where the diastereomers formed have different physical and chemical properties since they are not mirror images to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Baclofen, a drug used to treat muscle spasticity, for instance from spinal cord injuries, is one of the chiral drugs still sold in a racemic form. Previous research has shown that the two baclofen enantiomers have different bioactivities. , Accordingly, many processes have been developed to produce enantiopure baclofen or to separate the enantiomers of baclofen: asymmetric synthesis, chiral chromatography, , preferential crystallization, and resolution by diastereomeric salt formation. , The latter method is widely applied in industry since it is easy to scale up economically. The resolution occurs by forming diastereomeric salts from the racemate and a chiral resolving agent where the diastereomers formed have different physical and chemical properties since they are not mirror images to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the solid-state IR spectra of the starting materials and products of cocrystallization experiments allows establishing the formation of a new solid phase since changes in the vibrations of functional groups occur due to changes in the interaction patterns, particularly when hydrogen bonding motifs are varying [62][63][64]. The IR spectra of CTD (polymorph I), CAF, and CTD-CAF are shown in Figure 7, with the IR spectra of CTD and CAF matching with previously reported data [10,65].…”
Section: Analysis By Ir Spectroscopymentioning
confidence: 99%
“…In addition, baclofen has been recently approved in France as an alternative medication to treat alcohol dependence (Reade, 2021). Considering those new developments, the establishment of synthetic routes towards enantiopure (R)-baclofen were discussed recently (Co ´rdova-Villanueva et al, 2018;Gendron et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%